Parametric Study of the Vibration Transmissibility for the Rubber Mount of the Seawater-Conveying Pipe in a Ship - Han, Hyung-Suk; Jeong, Weui-Bong (Journal of the Society of Naval Architects of Korea, 2009)
Pipe system widely used in a ship is usually attached to the hull of a ship, and its vibration lead to structure-borne noise. Rubber mount is usually used as a vibration isolator of a pipe in a ship. In this paper, the effects of several factors, besides the stiffness and damping of the rubber mount, on vibration-isolating performance are taken into consideration. The parameters considered in this paper are hardness of the rubber material, painting on the rubber and deformation from clamping. Through the results of parametric study, the effective specifications of rubber mount are suggested to improve vibration-isolating performance. The performance under fluid flowing condition is calculated numerically and verified experimentally. KCI Citation Count: 0